1995
DOI: 10.1002/j.1460-2075.1995.tb07336.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the superantigen staphylococcal enterotoxin type A.

Abstract: Staphylococcal enterotoxins are prototype superantigens characterized by their ability to bind to major histocompatibility complex (MHC) class II molecules and subsequently activate a large fraction of T‐lymphocytes. The crystal structure of staphylococcal enterotoxin type A (SEA), a 27 kDa monomeric protein, was determined to 1.9 A resolution with an R‐factor of 19.9% by multiple isomorphous replacement. SEA is a two domain protein composed of a beta‐barrel and a beta‐grasp motif demonstrating the same genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
144
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 38 publications
3
144
0
Order By: Relevance
“…The structure and function properties of SEA have been well characterized (Abrahmsén et al, 1995;Hudson et al, 1995;Schad et al, 1995). To reduce the systemic toxicity, a major drawback in the use of wild-type SEA (Alphaug et al, 1998), a substitution of Asp 227 has been made.…”
Section: Discussionmentioning
confidence: 99%
“…The structure and function properties of SEA have been well characterized (Abrahmsén et al, 1995;Hudson et al, 1995;Schad et al, 1995). To reduce the systemic toxicity, a major drawback in the use of wild-type SEA (Alphaug et al, 1998), a substitution of Asp 227 has been made.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, zinc was not found in the structure of SEB (16,17), which shares 86% sequence homology with SECs. The zinc ligation in the crystal structures of SEA (18,19), SED (20) 1 The abbreviations used are: SE, staphylococcal enterotoxin; TSS, toxic shock syndrome; SAg, superantigen; TCR, T cell receptor; MHC, major histocompatibility complex; ICP MS, inductively coupled plasma mass spectrometry; SEC, staphylococcal enterotoxin in the type C serogroup. (21), and SEH (22) is found at a different site on the external face of the ␤-sheet wall in the C terminus large domain.…”
mentioning
confidence: 99%
“…From these results, the neutralizing epitope of SEA responsible for emetic activity of the toxin may consist in the three peptides regions corresponding to amino acid residues 121-140, 141-160 and 161-180. Based on the three-dimensional structure of SEA molecule [19], these regions are all located on the same domain and the same side of SEA. On the other hand, mutation analysis in SEA and use of different recombinant SEA molecules suggested that residues 47, 61 and 225 are important for emetic activity in monkey [5,7].…”
Section: Discussionmentioning
confidence: 99%